2019
DOI: 10.1097/rct.0000000000000772
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Magnetic Resonance Imaging in the Oncology Setting: An Overview and Update on Recent Advances

Abstract: Whole-body magnetic resonance imaging is becoming an important tool in oncology as a nonirradiating imaging technique since recent technological advances allowed the incorporation of high-quality imaging in an adequate time. Moreover, the noninjection of radioisotope/intravenous contrast, low cost compared with traditional nuclear medicine techniques, and fast acquisition times are another distinct feature. Thus, the purpose of this article is to review the whole-body magnetic resonance imaging protocol and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Susceptibility artefacts represent another challenge that may degrade image quality and mask lesions, leading to false negative results [11]. False positive results may be obtained due to the so-called "T2-shine through" effect, where lesions with high T2 signal may be mistaken for areas of restricted diffusion [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility artefacts represent another challenge that may degrade image quality and mask lesions, leading to false negative results [11]. False positive results may be obtained due to the so-called "T2-shine through" effect, where lesions with high T2 signal may be mistaken for areas of restricted diffusion [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of metastasis in cancer patients is an essential step for timely management and a positive outcome. Osseous metastasis can be spinal or appendicular and extra-osseous metastasis can involve the liver, lung, and lymph nodes [1][2][3][4]. Different imaging modalities are used for the detection of osseous and extra-osseous metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-body protocols have evolved since they were first used 2 decades ago. Now it combines optimal anatomical information from 2 anatomical sequences: T1-weighted and short time inversion recovery (STIR), while functional qualitative and quantitative data, including DWI with ADC measurement, provide useful information from multiple regions of the body [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the feasibility and reliability of whole-body CT and MRI, especially with diffusion-weighted imaging (DWI), as an alternative tool for staging of lymphoma, determination of tumour burden, prognostic biomarker, and assessment of treatment response [4][5][6][7]. Quantitative assessment of lymphoma was carried out in previous studies using apparent diffusion coefficient (ADC) measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of metastasis in cancer patients is an essential step for timely management and a positive outcome. Extra-osseous metastasis can affect the liver, lung, and lymph nodes, while osseous metastasis can be spinal or appendicular [2][3][4][5]. Different imaging modalities are used for the detection of osseous and extra-osseous metastasis.…”
Section: Introductionmentioning
confidence: 99%